Research on Multi-disciplinary Design Optimization for Marine Power Plant - Yin, Hongsheng; Liu, JinLin; Zeng, FanMing (2017 10th International Symposium on Computational Intelligence and Design (ISCID), 2017)
Based on the current problem that overall design of the marine power plant lacks effective method and inter-disciplinary coupling analysis to meet technical and tactical requirements, Multidisciplinary Design Optimization was proposed to apply to the overall design process of marine power plant. Firstly, combined with the development of MDO, decomposition of disciplines, academic coupling, decoupling and other key technologies about marine power plant are studied to put forward MDO method of overall design for ship power plant. Furthermore, based on the calculation of shaft alignment and lateral vibration, an example of the Multidisciplinary Design Optimization of the shaft was given. Meanwhile, MDO strategy, optimization algorithm, approximation method, sensitivity analysis, calculation support platform design were studied. Through the research in the paper, a new scientific method, which meets the technical and tactical requirement of overall design process about marine power plant was put forward. This method would be used as a reference to improving the overall design of marine power plant.